The Influence of Cooperative Learning Model Type of Group Investigation (Gi) Assistant Media Counting Funny on Understanding Multiplication Concept (Research on Class III Students of MI Muhammadiyah Sawangan) - Wulandari, Catur (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the group investigation (GI) cooperative learning model with the help of funnel counting media on the understanding of multiplication concepts in third grade students of MI Muhammadiyah Sawangan. This research is a type of pre-experimental research with one group pretest-posttest model. The research subjects were all third grade students of MI Muhammadiyah Sawangan with a saturated sampling model. The sample taken as many as 16 students. The method of data collection was carried out using an objective test in the form of multiple choice. Test the validity of the test instrument using the product moment while the reliability test using Cronbach alpha. The analysis prerequisite test used the normality test. Data analysis used paired sample t-test paramatretic test technique with the help of SPSS version 23.00 for windows program. The results of this study indicate that the group investigation (GI) cooperative learning model with the help of funnel counting media has an effect on understanding the concept of multiplication. This is evidenced by The results of the paired sample t-test analysis showed that the significance value was 0.000, which means less than 0.05 (sig 0.000 <0.05). The calculation of the average score of the objective posttest objective test of 74.00 which is higher than the average value of the pretest objective test of 52.6.